2015
DOI: 10.1007/s10488-015-0690-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Change and Outcome Trajectories Across Levels of Care in a Mental Health System for Youth

Abstract: Knowledge of mental health treatment outcome trajectories across various service types can be valuable for both system- and client-level decision-making. Using longitudinal youth functional impairment scores across 2807 treatment episodes, this study examined outcome trajectories and estimated the number of months required for reliable change across nine major services (or levels of care). Results indicate logarithmic improvement trajectories for a majority of levels of care and significant differences in time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…This study tested variables relationships with speed of improvement. For some factors, findings were broadly consistency with the literature e.g., higher baseline scores predict faster improvement [12,38,15], however, for others findings were more discrepant. Firstly, we found that older adolescents had higher baseline scores, but also improved more rapidly than younger ones.…”
Section: Discussionsupporting
confidence: 80%
“…This study tested variables relationships with speed of improvement. For some factors, findings were broadly consistency with the literature e.g., higher baseline scores predict faster improvement [12,38,15], however, for others findings were more discrepant. Firstly, we found that older adolescents had higher baseline scores, but also improved more rapidly than younger ones.…”
Section: Discussionsupporting
confidence: 80%
“…This is in line with earlier studies that demonstrate a curvilinear outcome response, with initial rapid improvement rates followed by a decelerating curve over the course of treatment. 30,[94][95][96] The moderator analysis suggested that, in line with previous research, informant perspective moderates outcomes, with clinician reports generally documenting greater improvements than self-or parent-reports. 97 This highlights the need to ensure the views of patients themselves are considered wherever possible if patient shared decisions and empowerment are to be made a reality.…”
Section: Discussionsupporting
confidence: 66%
“…27 There may be several person-and treatmentrelated variables that act as moderators, including but not limited to problem type, comorbidity, treatment length, and outcome informant. [28][29][30][31][32][33] Outcome moderation within this context warrants further investigation and is crucial for delineating the factors that may enhance or reduce clinical effectiveness in routine practice. This information may prove to be decisive in enabling clinicians to be prescriptive in their choice of treatment based on the likely outcome on an individual basis.…”
mentioning
confidence: 99%
“…MTPS treatment targets are moderately stable across treatment months (Nakamura et al, 2007), are predictably associated with Diagnostic and Statistical Manual diagnoses and factor in an expected way (Daleiden et al, 2004; Love et al, 2018; Nakamura et al, 2007). Significant associations have been found between MTPS progress ratings and other measures of treatment outcome, including discharge status and change in functioning (Jackson et al, 2017). Substance use is the critical target for this study serving both as an inclusion criteria and as the basis for the associated progress ratings used as the measure of substance use treatment gains.…”
Section: Methodsmentioning
confidence: 99%